Bioequivalence Study of the Two Products of Efavirenz by Validated Analytical Method: Bioequivalence Study of the Two Products of Efavirenz by Validated Analytical Method - Mukhopadhyay, Dr. Goutam (International Journal of Pharmaceutical & Biological Archive, 2018)
The aim of this study was to find whether the bioavailability of a 600 mg efavirenz capsule (E.F.600 capsule, test) produced by Macneil and Argus Pharmaceutical Ltd. was equivalent to the tablet EFAVIR produced by the Cipla Ltd. (reference preparation). The pharmacokinetic parameters assessed in this study were area under the plasma –concentration time curve 0–96 h (AUCt), area under the plasma concentration time curve from time 0 to ∞ (AUCinf), the peak plasma concentration of drug (Cmax), time needed to achieve the peak plasma concentration (tmax), and the elimination half-life (t½). This was a randomized, single-blind, two-period, crossover study which included 20 healthy adult male and female subjects under fasting conditions. In each of the two study periods (separated by a washout of 1 week), single dose of test or reference drug was administered. Blood samples were taken up to 96 h past dose, the plasma was separated, and the concentrations of efavirenz were determined by high-performance liquid chromatography -UV method. Bioavailability and bioequivalence studies play a key role during the phase of drug development for both innovator drugs and generic drugs and thus have gained a great attention over the past few decades. Bioequivalence study is used to introduce generic drugs of innovator drugs at a lower cost. Hence, a thorough understanding of these bioavailability/bioequivalence studies is required.